1997
DOI: 10.1002/(sici)1098-2744(199712)20:4<355::aid-mc5>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Altered in vitro spreading and cytoskeletal organization in human glioma cells by downregulation of urokinase receptor

Abstract: The interaction of urokinase-type plasminogen activator (uPA) with its cell-surface receptor (uPAR) is implicated in diverse biological processes such as cell migration, tissue remodeling, and tumor cell invasion. Recent studies indicated that uPAR can act as an extracellular matrix receptor during cell adhesion. Recently, we showed that transfection of the human glioma cell line SNB19 with antisense uPAR resulted in downregulation of uPAR at both the mRNA and protein levels. In this study, we used SNB19 to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Whereas the mitogenic effects of uPA are widely known (25), the role of uPAR has not been as clearly delineated. In fact, some previous uPAR blocking studies using a specific monoclonal antibody or uPAR antisense reported no effect on uPA-induced proliferation, consistent with our current findings that uPA-induced kidney fibroblast proliferation is independent of uPAR expression (25,30,34). In fact, in the present study, the opposite response was observed, with either genetic uPAR deficiency or pretreatment with a uPAR-blocking antibody associated with higher rates of uPA-induced proliferation than with control wild-type fibroblasts.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas the mitogenic effects of uPA are widely known (25), the role of uPAR has not been as clearly delineated. In fact, some previous uPAR blocking studies using a specific monoclonal antibody or uPAR antisense reported no effect on uPA-induced proliferation, consistent with our current findings that uPA-induced kidney fibroblast proliferation is independent of uPAR expression (25,30,34). In fact, in the present study, the opposite response was observed, with either genetic uPAR deficiency or pretreatment with a uPAR-blocking antibody associated with higher rates of uPA-induced proliferation than with control wild-type fibroblasts.…”
Section: Discussionsupporting
confidence: 91%
“…Dynamic alterations in the organization of the actin cytoskeleton play a critical role in tumor‐associated progression such as invasion and metastasis (Chintala et al. 1997, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous results have demonstrated the possible involvement of Ras-PI3k in the uPAR-mediated signaling cascade (9). We have shown that the absence of uPAR in human glioma cells leads to morphological changes associated with decreased spreading and a disorganized cytoskeleton resulting in altered cell morphology (10). Cathepsin B is known to be associated with uPAR and its integrin-mediated signaling ability (11).…”
Section: Introductionmentioning
confidence: 95%